Characteristics of Anti-Contactin1 Antibody-Associated Autoimmune Nodopathies With Concomitant Membranous Nephropathy - Xu, Qianhui; Liu, Shuhu; Zhang, Peng; Wang, Zhen; Chang, Xin; Liu, Yulu; Yan, Jiahe; He, Ruirong; Luo, Xiaoguang; Zou, Liang-Yu; Chu, Xiaofan; Guo, Yi; et al. (Frontiers in Immunology, 2021)
Background: The concurrence of anti-contactin 1 (CNTN1) antibody-associated chronic inflammatory demyelinating polyneuropathy (CIDP) and membranous nephropathy (MN) has previously been reported in the literature. CIDP with autoantibodies against paranodal proteins are defined as autoimmune nodopathies (AN) in the latest research. In view of the unclear relationship between CIDP and MN, we performed a case study and literature review to investigate the clinical characteristics of anti-CNTN antibody-associated AN with MN. Methods: We detected antibodies against NF155, NF186, CNTN1, CNTN2, CASPR1 and PLA2R in blood samples of a patient with clinically manifested MN and concomitant peripheral neuropathy via double immunofluorescence staining and conducted a quantitative measurement of anti-PLA2R IgG antibodies via enzyme-linked immunosorbent assay (ELISA). Case reports of anti-CNTN1 antibody-associated AN, anti-CNTN1 antibody-associated AN with MN, and CIDP with MN were retrieved through a literature search for a comparative analysis of clinical characteristics. The cases were grouped according to the chronological order of CIDP and MN onset for the comparison of clinical characteristics. Results: A 57-year-old man with anti-PLA2R positive MN was admitted to the hospital due to limb numbness, weakness, and proprioceptive sensory disorder. He was diagnosed with anti-CNTN1 antibody-associated AN and recovered well after immunotherapy. Our literature search returned 22 cases of CIDP with MN that occurred before, after, or concurrently with CIDP. Good responses were achieved with early single-agent or combination immunotherapy, but eight out of the 22 patients with CIDP and concomitant MN ultimately developed different motor sequelae. Five patients had anti-CNTN1 antibody-associated AN with MN. Among these patients, males accounted for the majority of cases (male:female=4:1), the mean age at onset was late (60.2±15.7 years, range 43–78 years), and 40% had acute to subacute onset. Clinical manifestations included sensory-motor neuropathy, sensory ataxia caused by proprioceptive impairment, and elevated cerebrospinal fluid protein levels. Conclusion: The age at onset of CIDP with MN was earlier than that of anti-CNTN1 antibody-associated AN. MN may occur before, after or concurrently with CIDP. The early detection and isotyping of anti-CNTN1 and anti-PLA2R antibodies and the monitoring of isotype switching may be essential for suspected CIDP patients.